Las opiniones consultivas de la Corte Interamericana en el control de convencionalidad - Sagüés, Néstor Pedro (Pontificia Universidad Católica del Perú, 2015)
This article discusses the conventionality control according to the jurisprudence of the interamerican Court of Human rights. Particularly, the author analyzes whether advisory opinions, like judgments, constitute the “controlling material” of the conventionality control. in this way, the author presents and discusses theses derived from the referred jurisprudence, to conclude that the interpretative guidelines contained in advisory opinions of the interamerican Court of Human rights constitute the “controlling material” under certain circumstances.

El presente artículo aborda el control de convencionalidad según la jurisprudencia emitida por la Corte interamericana de Derechos Humanos. En particular, el autor se detiene a analizar si las opiniones consultivas, al igual que una sentencia, pueden constituir el “material controlante” del control de convencionalidad. De esta forma, el autor expone y examina las principales tesis que se derivan de la referida jurisprudencia, para concluir los lineamientos interpretativos contenidos en opiniones consultivas de la Corte interamericana de Derechos Humanos valen como el “material controlante” bajo ciertas circunstancias.
The advisory opinion of the Interamerican Court in the conventionality control
Keywords: Advisory Opinion; Interamerican Court Of Human Rights; Conventionality Control; International Law; Constitutional Law; Opinión Consultiva; Corte Interamericana De Derechos Humanos; Control De Convencionalidad; Derecho Internacional; Derecho Constitucional; https://purl.org/pe-repo/ocde/ford#5.05.00